2019
DOI: 10.21203/rs.2.10883/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of Vitamin D Receptor gene polymorphisms in colorectal cancer risk

Abstract: Background: Vitamin D deficiency has been associated with increased colorectal cancer (CRC) incidence risk and mortality. Vitamin D mediates its action through binding of the vitamin D receptor (VDR) and polymorphisms of the VDR might explain these inverse associations. Methods: The aim of the study was the investigation of TaqI, ApaI, FokI and BsmI polymorphisms of the VDR gene for their relevance to colorectal carcinogenesis and progression. Peripheral blood was obtained from 397 patients with early operable… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…As described previously by our group and others, TLR and VDR polymorphisms have been significantly associated with cancer development, progression, and, therefore, patients' clinical outcome [18,19,49,50]. Linked to the fact that TLR and the VDR genes play an important role in the prevention and elimination of infections, their mutations result in the impaired activation of these receptors, decreased response to microbial particles, and impaired homeostasis, thus leading to carcinogenesis and disease progression [51][52][53][54][55][56].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…As described previously by our group and others, TLR and VDR polymorphisms have been significantly associated with cancer development, progression, and, therefore, patients' clinical outcome [18,19,49,50]. Linked to the fact that TLR and the VDR genes play an important role in the prevention and elimination of infections, their mutations result in the impaired activation of these receptors, decreased response to microbial particles, and impaired homeostasis, thus leading to carcinogenesis and disease progression [51][52][53][54][55][56].…”
Section: Discussionmentioning
confidence: 91%
“…TLR2 (−196 to −174 bp), TLR4 (Asp299Gly and Thr399Ile), and TLR9 (T1237C and T1486C) polymorphisms and TaqI, ApaI, FokI, and BsmI polymorphisms of the VDR gene have been described previously [18,19], and their correlation with the presence of microbial DNA in the blood of CRC patients was investigated ( Table 3). A significant coexistence was observed between the detection of all four different microbial DNA fragments with all different VDR and TLR polymorphisms.…”
Section: Correlation Of Microbial Dna Presence and Tlr And Vdr Polymomentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction of vitamin D with the immune system is the important factor that activates both inherent and acquired immune systems. In recent years, with increasing knowledge about the effects of vitamin D, researchers have studied its influence in a variety of diseases and different kinds of cancer [ 24 , 25 ]. The data indicates that vitamin D is involved in the regulation of immune responses for both innate and adaptive immunity.…”
Section: Discussionmentioning
confidence: 99%
“…However, we also found that rs2228570, rs1544410 and rs731236 were not significantly associated with RCC risk, adjusted for covariates. Several previous studies have reported the association between polymorphisms in VDR SNPs and risk of cancer, such as breast cancer and its survivors [20], colorectal cancer [21], lung cancer [22], advanced gallbladder cancer [23], bladder cancer [24], gastric cancer [25] and oral cancer [26]. To date, limited number of studies on relationship between VDR SNPs and RCC risk were performed, in addition, these previous studies could not obtain consistent results.…”
Section: Discussionmentioning
confidence: 99%